2013
DOI: 10.4236/mrc.2013.23a001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Photocatalytic Behaviors of Ca Mn Co-Doped BiFeO<sub>3</sub> Nanofibres

Abstract: Ca and Mn co-doped BiFeO 3 ultrafine nanofibres were prepared with the purpose of improving magnetic and photocatalytic performances of the one-dimensional multiferroic material. Impurity phase introduced by both Bi fluctuation and Mn substitution can be suppressed by Ca doping and a space group transition from R3c to C222 can also be triggered by Bi-site doping. With co-substitution of Mn into iron site, the Ca 0.15 Bi 0.85 Mn 0.05 Fe 0.95 O 3 nanofibres presented a larger saturation magnetization than the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In each method there are parameters to play with in order to improve the properties of the required materials. A lot of perovskite oxides have been synthesized such as tantalate [39][40][41][42][43], titanate [14,[44][45][46][47][48][49][50], ferrite, [51,52] vanadium-and niobium-based perovskites [53][54][55][56], and manganites [57,58] and they have shown visible light photocatalytic activity as a result of their unique electronic properties and crystal structures [59]. The reduced band-gap energy values in the doped alkaline rare-earth transition metal perovskite-like structure oxides focus more attention because this property enhances the separation of charge carriers (photogenerated electrons and holes) [60].…”
Section: Perovskites As Photocatalyticmentioning
confidence: 99%
“…In each method there are parameters to play with in order to improve the properties of the required materials. A lot of perovskite oxides have been synthesized such as tantalate [39][40][41][42][43], titanate [14,[44][45][46][47][48][49][50], ferrite, [51,52] vanadium-and niobium-based perovskites [53][54][55][56], and manganites [57,58] and they have shown visible light photocatalytic activity as a result of their unique electronic properties and crystal structures [59]. The reduced band-gap energy values in the doped alkaline rare-earth transition metal perovskite-like structure oxides focus more attention because this property enhances the separation of charge carriers (photogenerated electrons and holes) [60].…”
Section: Perovskites As Photocatalyticmentioning
confidence: 99%
“…Doping induced improvement in photocatalytic activities have also been studied for those semiconducting magnetic materials (e.g. Ca, Mn codoped BiFeO 3 nanofibers [66]); Further the heterojunction based semiconductors are also made with the semiconducting magnetic materials (Bi 2 O 3 /SrFe 12 O 19 [67], ZnFe 2 O 4 /BiVO 4 [68]) to enhance the photocatalytic reactions.…”
Section: Catalytic and Photocatalytic Applicationsmentioning
confidence: 99%
“…Optical and PC properties of Mn-involved co-doping BFO have also been recently studied. For example, researchers observed that Ba/Ca and Mn co-doped BFO nanofibers delivered enhanced PC performances [20,21]; Vinay et al obtained a photo-induced current of about 250-fold in Ce and Mn co-doped BFO thin films at zero bias in a PV test [5]. However, few studies have focused on the effects of the Mn single doping of BFO on PEC properties.…”
Section: Introductionmentioning
confidence: 99%